PERAN PESANTREN DALAM PEMBENTUKAN KARAKTER SANTRI (Studi Kasus Di Pondok Pesantren Darunnajah Kebonagung Sawahan Nganjuk ) - Dewi Murbhitoh; Adibah Jauhari; Abdul Rouf (Arsy : Jurnal Studi Islam, 2020)
History note, that pesantren have very big role in following to move forward education in indonesia during the time. Excess of pesantren lay its existence which multifungsional that as; education institute, mission, and struggle. So that pesantren do not fail to go forward him with other education institute, hence one of the effort which conducted by pesantren by developing formal education and him of no formal education. This matter also which conducted by Maisonette of Pesantren Darunnajah Kebonagung. Early from maisonette pesantren of Darunnajah as one of the pesantren which it there are education which wish to form character of student, hence in this Thesis of writer interest to perform a furthermore research to existence of maisonette pesantren of this Darunnajah Kebonagung with formula of problem of that is: 1). How Pattern Education of Pesantren in forming character of student in Maisonette of Pesantren Darunnajah Kebonagung, 2).How Role of Pesantren in forming character of student in Maisonette of Pesantren Darunnajah Kebonagung. Pursuant to existing formula, target of this research that is: To know Pattern Education of Pesantren in forming character of student in Maisonette of Pesantren Darunnajah Kebonagung and To know Role of Pesantren in forming character of student in Maisonette of Pesantren Darunnajah Kebonagung. this Research type is research qualitative, method used to obtain get data is observation method, interview, and documentation. collected data is later then compiled and analysed by using descriptive qualitative. Through step reduce data, compilation of data and intake of conclusion. Result of this research indicate that Education Of Maisonette of Pesantren this Darunnajah have been able to play a part in to form character of student. Education pattern is used in forming of character to santri in this research by giving good byword, with practice method and inuring, educative through ibrah ( taking Iesson), educative [pass/through] mauidzih ( giving of advise), educative through discipline, educative through independence. As for role of Maisonette pesantren of Darunnajah in forming character of Students seen to cover as counsellor, fasilitator, proofreader, inspirator, informator, motivator, evaluator. With a purpose to be formed its character of student which is Responsibility, Downright, Self-Supporting, discipline, and have respect.